2017
DOI: 10.1128/jcm.01757-16
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated Amoebic Appendicitis among HIV-1-Infected Individuals in Japan

Abstract: Entamoeba histolytica is not a common causative agent of acute appendicitis. However, amoebic appendicitis can sometimes be severe and life threatening, mainly due to a lack of awareness. Also, its frequency, clinical features, and pathogenesis remain unclear. The study subjects were HIV-1-infected individuals who presented with acute appendicitis and later underwent appendectomy at our hospital between 1996 and 2014. Formalin-fixed paraffin-embedded preserved appendix specimens were reexamined by periodic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Appendicitis was noted in up to 15% of Japanese HIV-infected patients presenting with appendicitis and undergoing appendectomy [ 38 ]. The only distinguishing feature was a higher median neutrophil count in those with amebic infection compared with those without in this series [ 38 ]. Ameboma, the development of tumor-like granulation tissue in the colonic lumen, can mimic colonic cancer.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Appendicitis was noted in up to 15% of Japanese HIV-infected patients presenting with appendicitis and undergoing appendectomy [ 38 ]. The only distinguishing feature was a higher median neutrophil count in those with amebic infection compared with those without in this series [ 38 ]. Ameboma, the development of tumor-like granulation tissue in the colonic lumen, can mimic colonic cancer.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…In contrast to our seroprevalence data, the national surveillance data of Japan from NESID pragmatically show that the annual number of diagnosed cases of amebiasis (1151 in 2016) is not only much lower than that of syphilis (4575 cases), it is also lower than that of HIV-1 (1443 cases) 22 23. Our results suggest that the endemicity of amebiasis in Japan is currently underestimated, thereby remaining a neglected disease in Japan despite frequently reported life-threatening cases of amebiasis 24–27. Interestingly, in this study, all individuals who were seropositive for E. histolytica were HIV-1 negative, whereas regression analysis identified that seropositivity for syphilis by TPHA was an independent risk factor of a positive result for anti- E. histolytica antibody.…”
Section: Discussionmentioning
confidence: 52%
“…In a Japanese contribution, the amebic element was complicated by HIV-1-infection [6]. This was not the issue in our case.…”
Section: Discussionmentioning
confidence: 58%